Long‐term (6 and 12 months) follow‐up of two prospective, randomized, controlled phase III trials of photodynamic therapy with BF‐200 ALA and methyl aminolaevulinate for the treatment of actinic keratosis. (25th March 2013) - Dirschka, T.; Radny, P.; Dominicus, R.; Mensing, H.; Brüning, H.; Jenne, L.; Karl, L.; Sebastian, M.; Oster‐Schmidt, C.; Klövekorn, W.; Reinhold, U.; Tanner, M.; et al.
Abstract : Summary Background Two phase III trials of photodynamic therapy (PDT) with BF‐200 ALA, a recently approved nanoemulsion formulation of 5‐aminolaevulinic acid (ALA) demonstrated high clearance rates in mild‐to‐moderate actinic keratosis (AK). The comparison to a registered methyl aminolaevulinate (MAL) cream demonstrated significantly superior total patient clearance rates. Objectives To evaluate long‐term efficacy and safety of PDT for AK 6 and 12 months after the last PDT with BF‐200 ALA, MAL or placebo. Methods The follow‐up phase (FUP) was performed with patients of two phase III studies. Both studies compared BF‐200 ALA with placebo, one of the studies additionally with MAL. Overall recurrence rates and various subgroups (light source, lesion severity, lesion location, complete responders after first PDT) were assessed 6 and 12 months after the last PDT. Results Recurrence rates were similar for BF‐200 ALA and MAL, with a tendency to lower recurrence rates for BF‐200 ALA. The proportion of patients who were fully cleared during PDT and remained completely clear for at least 12 months after PDT were 47% for BF‐200 ALA (both studies) and 36% for MAL treatment. The subgroup that was illuminated with narrow wavelength LED lamps reached 69% and 53% for BF‐200 ALA (both studies, respectively) and 41% for MAL. No safety concerns were reported. Conclusions The FUP data confirmed the high efficacy and safety of PDT with BF‐200 ALA. The slightly lower recurrence rates after BF‐200 ALA treatment compared with MAL treatment enhanced the better treatment outcome due to the significantly superior efficacy. Abstract : What's already known about this topic? BF‐200 ALA is a stable nanoemulsion‐based gel formulation of 5‐aminolaevulinic acid (ALA) for photodynamic therapy (PDT) of actinic keratosis (AK), which demonstrated significantly higher efficacy compared with a registered methyl aminolaevulinate (MAL) cream. What does this study add? This study gives 6‐ and 12‐month follow‐up results of two pivotal phase III studies with BF‐200 ALA for PDT of AK in comparison to placebo and a registered MAL cream. It provides a comparison of recurrence rates after use of different light sources for PDT of AK. See also the Commentary by Babilas